Evaluating the Depression Level Based on Facial Image Analyzing and Patient Voice - Ramos-Cuadros, Alexander (2023)
Depression is regarded as a widespread mental condition that affects people of all ages. It has a negative impact on a variety of aspects of life, including mood, vigor, and interests in enjoying activities. In the most severe cases, depression can also result in suicide. creating the chance for collaboration between mental health professionals and the use of technical tools to enhance the assessment of the severity of depression to offer the patient with an ideal clinical diagnosis and an appropriate referral to begin treatment. The COVID-19 epidemic in Peru has decreased face-to-face interaction and quick access to medical professionals, making it more difficult for patients’ mental health to be identified or treated effectively, which results in the disease becoming chronic, psychological suffering, and high costs associated with specialized care. The implementation of a technology model that assesses degrees of recurrent depression by examining facial photos and voice to identify the chronicity of depressive symptoms in young Peruvians is thus one of the research’s problems. Our findings demonstrate that, based on the functions of the mobile application, adolescent patients were predisposed to complete a self-administered depression questionnaire in a simulated setting with an optimal feeling of satisfaction and usefulness.